2020
DOI: 10.1021/acscatal.0c00907
|View full text |Cite
|
Sign up to set email alerts
|

Dispersed Nickel Boosts Catalysis by Copper in CO2 Hydrogenation

Abstract: The empirical optimization of the preparation of catalytically active copper-containing catalysts is far more advanced than the fundamental understanding of the catalyst performance because of the structural complexity of the catalysts. Here, we demonstrate the interplay between the catalyst structure and CO 2 hydrogenation on Cu catalysts boosted with nickel species. The nickel dispersion on copper markedly affects the CO 2 dissociation activity and catalytic reaction pathways, thus resulting in distinctive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 54 publications
1
55
0
1
Order By: Relevance
“…Inspired by the catalysts with SMSI for weak adsorption of the *CO intermediate to selectively obtain the CO product in CO 2 hydrogenation, it is reasonable that construction of alloyed metal catalysts with variable adsorption of *CO intermediate could be adjusted by the alloyed compositions and supports. 99,100 Recently, alloys of PtCo, NiFe, CuNi and NiAu 16,20,21,101,102 are reported for tuning product selectivity in CO 2 hydrogenation.…”
Section: Alloy-based Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired by the catalysts with SMSI for weak adsorption of the *CO intermediate to selectively obtain the CO product in CO 2 hydrogenation, it is reasonable that construction of alloyed metal catalysts with variable adsorption of *CO intermediate could be adjusted by the alloyed compositions and supports. 99,100 Recently, alloys of PtCo, NiFe, CuNi and NiAu 16,20,21,101,102 are reported for tuning product selectivity in CO 2 hydrogenation.…”
Section: Alloy-based Catalystsmentioning
confidence: 99%
“…Moreover, addition of promoters/additives might result in the formation of new active sites and interfaces for CO 2 adsorption and transformation. Wang et al 20 More importantly, the simple and uniform structure of Ni-in-Cu catalyst provides a model for mechanism investigation to identify the reaction routes and active sites. By in-situ DRIFTS and XPS studies, the CO 3 2-, CO 2 δand HCO 3species are observed on the catalyst surface, giving decreased signals during the CO 2 hydrogenation, which indicate their important roles as the intermediates for CO formation.…”
Section: Alloy-based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The copper-metal/metal oxide (Cu-MO x ) interface has been characterized as active sites for the CO 2 conversion to chemicals [123,146,186,[189][190][191][192][193]. Theoretical studies on Cu/ZrO 2 catalysts showed high activity for intermediates formation at the Cu-ZrO 2 interface [123,[189][190][191].…”
Section: (Ii) Cu-interfacial Sitesmentioning
confidence: 99%
“…选择性 [61] 和常春然等 [62] 用密度泛函理 论(Density Functional Theory, DFT)对稀土金属氧化物活 化甲烷过程中 C-H 键的解离进行了研究, 其中龚学庆 等 [61] [63] 、丁醇 [64] 、巴豆醛 [65] 等高 附加值的化学品, 乙醛/乙醇混合物 aldol 加成的反应路 径如图式 1. [66] .…”
unclassified